Wakaf dan Energi Terbarukan - Rahman Ali Fauzi (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2021)
This research aims to determine the potential of waqf and renewable energy and their benefits in reducing the impact of climate change. The research method used is qualitative research obtained from the results of studies of several research institutions engaged in waqf and energy. The data is collected and then translated through a descriptive method that emphasizes the potential for energy waqf that needs to be developed to respond to the impacts of climate change. The results of this study indicate that waqf and renewable energy have enormous potential in Indonesia. As a country with the largest Muslim population in the world, BWI estimates that the potential for waqf in Indonesia every year is 188 T. Likewise, as a country with a tropical climate with the sun shining all year round, Indonesia can become a leader in the development of solar energy with a potential of 4.8 KWh/m2 or equivalent to 112,000 GWp. The integration of waqf as a fund to finance the use of renewable energy has a positive role in reducing the impact of climate change, especially in Indonesia.